Designing a Phygital Prosthesis for Urban Spaces: Merging Digital and Physical Realities - Cevallos Andrade, Daniel; Del Blanco García, Federico Luis (Street Art & Urban Creativity, 2025)
The "phygital" paradigm enables the creation of speculative narratives in contemporary human interaction, particularly in the context of the "new normal." The research explores the integration of physical and digital urban landscapes, aiming to create immersive experiences that could transform these environments. This effort results in the development of the Hyper-connector (prosthesis), an artifact that bridges the gap between physical and digital realms in public spaces. Acting as a facilitator, the Hyper-connector merges digital layers with physical spaces through human-computer interactions. This concept is made possible through advanced technologies, generative art, collaborative music, sound-reactive algorithms, and the Internet of Things. The article details the creation process of the Hyper-connector, addressing the potential of emerging technologies to overcome contemporary urbanism's limitations. Additionally, it explores how phygital prostheses could empower citizens to actively engage in the improvement of public spaces.